MATHEMATICAL MODELING OF THERMOSTRESSED STATE OF CHILL MOLD WITH THE AIM OF INCREASING OF ITS RESISTANCE - A. N. Chichko; L. V. Markov (Литьë и металлургия)
The mathematical models for calculation of stresses in chill mold, arising at its filling with melt, are offered. The possibilities of modeling of dynamics of the shaped casting mold stressed state are shown by the example of casting ''grid”, produced by casting into chill mold.